RADT-36. PROSPECTIVELY ASSESSED TUMOR CONTROL AND TOXICITY OF BENIGN INTRACRANIAL PATHOLOGIES TREATED WITH AUTOMATED VMAT RADIOSURGERY – INITIAL 2 YEAR EXPERIENCE WITH FIRST 100 PATIENTS. (9th November 2020) - Thomas, Evan; Mullins, Clarence; Bredel, Markus; Dobelbower, Michael; Willey, Christopher; Spencer, Sharon; Guthrie, Barton; Riley, Kristen; Markert, James; Fiveash, John; Boggs, Drexell
Abstract: BACKGROUND: HyperArc is a treatment planning technology that automates treatment planning and delivery of single-isocenter VMAT radiosurgery (SRS). The technique generates high quality, rapidly deliverable plans. It is unknown whether HyperArc is effective for commonly-encountered, benign, intracranial conditions managed with SRS. Under IRB-approved prospective registry, we collected data on treatment planning/delivery, and clinical outcomes of non-malignant conditions managed with single-fraction or fractionated SRS since deployment in October 2017. METHODS: Patients received either single-fraction or fractionated SRS with HyperArc™ (Varian Medical Systems) between October 2017 & October 2019. Patients with < 3 months follow-up were censored. All patients treated received prescription dose to ≥ 99% of gross tumor volume without PTV expansion. All treatments were delivered on Varian Edge linac with 10MV flattening-filter free beam at 2400 MU/min with high-definition (2.5mm) multi-leaf collimator. Standard pathology-specific outcomes and toxicities were assessed. Significant CNS toxicity was defined as Grade 3 or higher event by CTCAE. RESULTS: Total of 100 targets (min=0.13cc, max=58.9cc) were treated. 55 received single-fraction SRS (12-22Gy), two received 2-fraction fSRS boost (12Gy) following fractionated treatment, and 43 received 5-fraction fSRS (25-30Gy). The most common pathology was meningioma (n=55), followed by AVM (n=18), non-secretory pituitary adenoma (n=12), acoustic schwannoma (n=9), secretory pituitary adenoma (n=3), glomus tumor (n=2), pineocytoma (n=1), and paraganglioma (n=1). Follow-up ranged from 1.2 to 19.5 months (median 7.2). There were three local failures, all in atypical meningiomas. One patient in the cohort experienced ≥Gr3 toxicity. Each radiosurgery session used median of 3 arcs, with median treatment and beam-on time of 12.03 and 2.3 minutes. Plan quality was excellent; median RTOG conformity was 1.15, and median Paddick GI was 3.52. CONCLUSION: Although HyperArc was developed for automated multiple-metastasis radiosurgery, we found it effective and efficient for benign intracranial indications too. Early clinical outcomes appear congruent with historical controls.